Prader-Willi Syndrome. About a Case - Carlos Enrique Cruz Carrazana; Claudia García Carrazana (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Prader-Willi syndrome is a rare genetic disease, characterized by hypothalamic-pituitary anomalies, which presents with severe hypotonia during the neonatal period and the first two years of life, with hyperphagia with a high risk of developing morbid obesity in childhood and adulthood; as well as learning difficulties and serious behavioral and / or psychiatric problems. A 17-years-old patient with white skin color is presented. The main manifestations of the patient showed: deviation of the palpebral fissure and alterations in the diameter, small hands and feet, obesity, hypogenitalism, diabetes mellitus, muscular dysfunction, mental deficiency, short stature, among others. The clinical criteria and results of complementary studies were compatible with the diagnosis of Prader-Willi syndrome. This case is presented because it is necessary to describe the clinical and genetic characteristics of patients with Prader-Willi syndrome, since it is a rare genetic disease with important compromise for the future life of those who suffer from it.